2016
DOI: 10.3233/nua-150058
|View full text |Cite
|
Sign up to set email alerts
|

Impact of high fat diets, prebiotics and probiotics on gut microbiota and immune function, with relevance to elderly populations

Abstract: Abstract. According to WHO, the number of people over 60 years of age is set to rise to 2 billion by 2050. Dysbiosis of microbial composition and impaired immune function have been observed in elderly persons compared to younger adults. As a result, the aging population has a higher disease risk than other age groups. In addition, high fat intakes have been observed to exert negative effects on microbial composition and immune function in murine studies. Elderly people have higher fat intakes than recommended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 142 publications
0
4
0
Order By: Relevance
“…The authors concluded that the results of this trial did not support their hypothesis (probiotics would reduce hepatic steatosis in humans). Notably, the effect of HFD on Bifidobacterium abundance also varies among studies, because some studies report an increased abundance upon HFD feeding [25], while others report a reduction in its abundance [30,39]. Similarly, the role of Lactobacillus is unclear: Jiang et al showed that the abundance of Lactobacillus was increased in the microbiota of NAFLD patients [40], suggesting a role in disease development, whereas probiotic treatment with Lactobacillus has been associated with beneficial effects in clinical NAFLD trials [6].…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that the results of this trial did not support their hypothesis (probiotics would reduce hepatic steatosis in humans). Notably, the effect of HFD on Bifidobacterium abundance also varies among studies, because some studies report an increased abundance upon HFD feeding [25], while others report a reduction in its abundance [30,39]. Similarly, the role of Lactobacillus is unclear: Jiang et al showed that the abundance of Lactobacillus was increased in the microbiota of NAFLD patients [40], suggesting a role in disease development, whereas probiotic treatment with Lactobacillus has been associated with beneficial effects in clinical NAFLD trials [6].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that a decrease in faecal pH value in subjects consuming fermented milk containing synbiotic of Lactobacillus casei Shirota strain and galactooligosaccharide for 1 and 2 weeks was attributable to the large production of intestinal organic acids by bacteria (butyric acid, propionic acid, and lactic acid) which later stimulated motility in colon [10]. Accordingly, decrease in faecal pH is affected by the number and activity of microorganisms in the The gut microbiota modulated by probiotics have the ability to ght against pathogenic bacteria by exploiting host' nutrients [28]. Subsequently, probiotics increase short-chain fatty acid (SCFA) in the bacterial colonies to reduce the pH of the colon environment and prevent pH-sensitive bacteria or pathogenic bacteria such as Enterobacteriaceae and Clostridia from healthy colon and improve nutrient absorption [10].…”
Section: Resultsmentioning
confidence: 99%
“…The gut microbiota modulated by probiotics have the ability to ght against pathogenic bacteria by exploiting host' nutrients [28]. Subsequently, probiotics increase short-chain fatty acid (SCFA) in the bacterial colonies to reduce the pH of the colon environment and prevent pH-sensitive bacteria or pathogenic bacteria such as Enterobacteriaceae and Clostridia from healthy colon and improve nutrient absorption [10].…”
Section: Discussionmentioning
confidence: 99%
“…However, Liu et.al. indicated that older adults often exceed recommended fat intake levels, which can increase their susceptibility to various disease risks [ 45 ].…”
Section: Discussionmentioning
confidence: 99%